2022
DOI: 10.1093/ndt/gfac174
|View full text |Cite
|
Sign up to set email alerts
|

Seroconversion rate after primary vaccination with two doses of BNT162b2 versus mRNA-1273 in solid organ transplant recipients: a systematic review and meta-analysis

Abstract: Background In the general population, the seroconversion rate after primary vaccination with two doses of an anti-SARS-CoV-2 mRNA vaccine reaches nearly 100%, with significantly higher antibody titers after mRNA-1273 vaccination compared to BNT162b2 vaccination. Here, we performed a systematic review and meta-analysis to compare the antibody response after two-dose mRNA-1273 versus BNT162b2 vaccination in solid organ transplant (SOT) recipients. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…Previous studies have shown a response rate to a mRNA vaccine of 48% [9] , 47.5% [10] , [11] and 44.9% [12] in patients with SOT, response rates significantly lower than that we observed in our OLT cohort (>80% RBD response rate). In the case of mRNA-1273 vaccine, a serological response of 93% [13] was seen vs. 100% in our study, and it is even higher than the liver subset analyzed in a recent SOT meta -analysis [12] , [14] . In the case of CoronaVac, in Uruguay [15] , a higher seroconversion rate, as compared with our cohort (36.5% vs. 13%) was observed.…”
Section: Discussioncontrasting
confidence: 63%
“…Previous studies have shown a response rate to a mRNA vaccine of 48% [9] , 47.5% [10] , [11] and 44.9% [12] in patients with SOT, response rates significantly lower than that we observed in our OLT cohort (>80% RBD response rate). In the case of mRNA-1273 vaccine, a serological response of 93% [13] was seen vs. 100% in our study, and it is even higher than the liver subset analyzed in a recent SOT meta -analysis [12] , [14] . In the case of CoronaVac, in Uruguay [15] , a higher seroconversion rate, as compared with our cohort (36.5% vs. 13%) was observed.…”
Section: Discussioncontrasting
confidence: 63%
“…Conditions associated with a favourable response at 6 months included initial vaccination with the mRNA 1273 vaccine, a positive humoral response at month 3, having received a third dose, and not being a KTR. The ability of the mRNA 1273 vaccine to induce stronger seroconversion than BNT162b2 was confirmed by other studies in HD patients [ 18 , 25 ] and in a meta-analysis of solid organ transplant patients (8 studies, 877 and 956 patients vaccinated with mRNA 1273 and BNT162b2, respectively) [ 26 ].…”
Section: Humoral Immunity After Sars-cov-2 Vaccinationsupporting
confidence: 53%
“…Nonseroconversion rates after 2 vaccinations were relatively low compared with other studies using mRNA-based SARS-CoV-2 vaccines, which could be due to the cohorts consisting of long-term KTRs (median time after transplantation is 7.6 and 6.9 y) with 60% to 70% of them using MMF/MPA. Also, all fully vaccinated KTRs received the mRNA-1273 vaccine, which has higher seroconversion rates and clinical effectiveness than BNT162b2 in KTRs with breakthrough infections, 50 , 51 which aids in the discussion of whether mRNA-1273 should be the preferred vaccine in these patients. Although the type of third vaccine did not influence the prediction of nonseroconversion, we see an improved discrimination in the much smaller mRNA-1273 cohort, the type of vaccine on which the model was originally built.…”
Section: Discussionmentioning
confidence: 99%